FRI0100 Treat to target: defining the optimum target to prevent radiographic erosion progression during the first year of treatment in an early rheumatoid arthritis cohort. (23rd January 2014) - Chitale, S.; Estrach, C.; Boswell, W.; Thompson, R.; Moots, R. J.; Goodson, N.
Abstract : Background: The target for most treat to target (T2T) regimes in early rheumatoid arthritis (eRA) is DAS28 remission. However, power Doppler ultrasound (PDUS) activity in patients in DAS28 remission is associated with radiographic progression (1 ). ACR-EULAR remission is more stringent (2 ) but is difficult to achieve and doesn't incorporate an imaging component. Combining clinical and PDUS information may provide an optimum remission assessment in eRA and predict radiographic outcomes. Objectives: To explore which remission criteria best predicted radiographic erosion non progression at 1-year (yr) in eRA patients. Methods: Newly diagnosed eRA (≤ 12 months symptoms) patients followed an initial T2T DMARD protocol in an early arthritis clinic. The treatment target was low inflammatory disease activity (LIDA:DAS28≤ 2.6 or absence of clinically swollen joints) with PDUS remission (PDUS signal of ≤ 1 in ≤ 1 joint) (3 ). Rates of DAS28 remission, ACR-EULAR remission (using Boolean criteria) and, PDUS remission with LIDA, within six months from diagnosis were assessed and used to predict radiographic erosive progression at 1-yr. A musculoskeletal radiologist and a rheumatologist, blinded to the clinical and remission data independently read the paired (baseline and 1-yr) hands/feet radiographs. Erosion progression was defined as increase in erosion size of existing erosions or new erosions at 1-yr. Results: 90 eRA patients with mean age 57.5 (SD 15.7) years, 63 (70%) female and 83 (92.2%) meeting ACR-EULAR RA classification criteria at baseline were identified. The 31 (34%) patients with baseline radiographic erosions were older than those without erosions (mean age 63 (SD 15) years vs 55 (SD 16) years, p=0.01). The median T2T period was 22 [14, 29] weeks. At 1-yr, 13 (15%) patients showed radiographic erosion progression. The numbers achieving each remission criteria by 6 months and proportions with erosion progression at 1-yr are shown [Table 1 ]. Achieving PDUS remission+ LIDA by 6 months was inversely associated with erosion progression with OR (adjusted for age and gender) 0.16; 95 % CI (0.03, 0.77). Conclusions: DAS28 remission was a poor predictor of radiological outcome highlighting the limitation of its use as a target in T2T regimes in eRA. ACR-EULAR remission strongly predicted radiographic erosion non-progression but very few patients (13%) achieved it. Nearly half of the eRA patients achieved PDUS remission+LIDA within 6 months with 6-fold increased odds of erosion non-progression at 1-yr. We suggest that T2T DMARD therapy protocols in eRA should be directed to more stringent remission targets in order to improve radiographic outcomes and PDUS remission + LIDA may be a practical and effective target for future T2T regimes. References: Brown AK et al. Arthritis Rheum 58 (10): 2958-67; Felson DT et al. Ann Rheum Dis 70 (3): 404-13; Chitale S et. al. Ann Rheum Dis 69 (S3 ): 493. Disclosure of Interest: None Declared